2020
DOI: 10.5551/jat.49841
|View full text |Cite
|
Sign up to set email alerts
|

High sdLDL Cholesterol can be Used to Reclassify Individuals with Low Cardiovascular Risk for Early Intervention: Findings from the Chinese Multi-Provincial Cohort Study

Abstract: A high-risk strategy has been implemented for lipid-lowering therapy in the primary prevention of cardiovascular disease. However, atherosclerosis and cardiovascular events are common among individuals with low cardiovascular risk. This study aimed to determine whether the small dense low-density lipoprotein cholesterol (sdLDLC) level can predict carotid atherosclerosis progression and identify high-risk individuals. Methods: Baseline sdLDLC and low-density lipoprotein cholesterol (LDLC) were measured in 808 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 39 publications
(57 reference statements)
0
22
0
Order By: Relevance
“…In fact, previous studies have demonstrated that apolipoprotein B, but not LDLc, was associated with the progression of carotid plaques [18] or the future risk of coronary heart disease [19]. Therefore, the use of LDLc to assess cholesterol-related carotid plaques risk might underestimate future cardiovascular risk compared with small dense LDLc [18]. Although we did not examine small dense LDLc in this study, to a certain extent, the use of non-HDLc to assess carotid plaques appears to be superior to LDLc as non-HDLc components include small dense LDLc.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, previous studies have demonstrated that apolipoprotein B, but not LDLc, was associated with the progression of carotid plaques [18] or the future risk of coronary heart disease [19]. Therefore, the use of LDLc to assess cholesterol-related carotid plaques risk might underestimate future cardiovascular risk compared with small dense LDLc [18]. Although we did not examine small dense LDLc in this study, to a certain extent, the use of non-HDLc to assess carotid plaques appears to be superior to LDLc as non-HDLc components include small dense LDLc.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, these ndings from mutually adjusted models indicate that other components of non-HDLc beyond LDLc might have more contribution to carotid plaques than LDLc. In fact, previous studies have demonstrated that apolipoprotein B, but not LDLc, was associated with the progression of carotid plaques [18] or the future risk of coronary heart disease [19]. Therefore, the use of LDLc to assess cholesterol-related carotid plaques risk might underestimate future cardiovascular risk compared with small dense LDLc [18].…”
Section: Discussionmentioning
confidence: 99%
“…A great deal of evidence indicated that the sdLDL was related to the incidence of atherosclerotic disease [5,13,24]. Several studies in different populations using various sdLDL measurements suggested that the sdLDL was related to the carotid intima thickness and in association with progression of carotid artery plaque [25][26][27]. Wu et al reported in 2019 that elevated sdLDL concentration was observed in ACS patients (n = 121) but not in healthy controls (n = 172) [28].…”
Section: Discussionmentioning
confidence: 99%
“…sdLDL-C has been found to be associated with increased risk for the development of CHD among the healthy participants with high or low risk of CVD [ 12 , 13 ] and increased risk for cardiovascular (CV) events in patients with stable CVD [ 14 ]. However, to date, few studies have explored the role of sdLDL-C in patients with acute coronary syndromes (ACS) undergoing percutaneous coronary intervention (PCI).…”
Section: Introductionmentioning
confidence: 99%